(untitled) (Sciences & Technologie. C, Biotechnologies, 2012)
Taking into account the re-emergence of leishmaniasis in the world, the geographic variability of its epidemiology and the growing numbers of travellers, a pilot study on the diagnosis of cutaneous leishmaniaasis and visceral leishmaniasis was undertaken in Constantine, one of the outbreak regions in eastern Algeria. A total of 143 cutaneous specimens and 108 bone marrow samples were collected on blotters and tested by real-time PCR. Results were compared with those of direct examination. Diagnosis, in CL, was positive for leishmaniasis in 81% of cases using PCR versus 48% of cases using microscopy. For VL, results were 26.9% for real time PCR versus 24% for microscopy exam. Real-time PCR showed a significant quantitative difference between patients for whommicroscopic diagnosis was positive and those for whom direct examination was negative. The results presented in thisstudy demonstrated the effectiveness and sensitivity of PCR in the diagnosis of cutaneous and visceral leishmaniasis from blotter specimens. This technique enabled in-field collection of specimens from each patient and provided prompt results. North- South cooperation based on the use of simple means for transmission of specimens for molecular diagnosis allowed creation of an effective partnership for daily diagnosis and promoted exchange between investigators in preparation for technology transfer